(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
Currently, slang is one of the most interesting language systems of modern linguistics. In this article, we will discuss special styles, that is, low-level words and phrases -colloquialism ("colloquial" - from the English language "word combinations characteristic of the style of conversation and expressions), slang ("slang" - from the English language "slang, simple, words typical of the oral lexicon"), general slang, special slang (slang and slang - special words) and vulgarism (rude we are talking about words).